Incidence and risk factors of injuries and their impact on academic success: A prospective study in PETE students. (30th January 2017) - Bliekendaal, S.; Goossens, L.; Stubbe, J. H.
Abstract : Injuries can have a major impact on the physical performance and academic career of physical education teacher education (PETE) students. To investigate the injury problem, risk factors, and the impact of injuries on academic success, 252 PETE students were followed during their first semester. Risk factor analysis was conducted by means of logistic regression analysis with a differentiation for upper body, lower body, acute, overuse, and severe injuries. An incidence of 1.26 injuries/student/semester was found. Most injuries involved the lower body (61%), were new injuries (76%), occurred acutely (66%), and were sustained during curricular gymnastics (25%) or extracurricular soccer (28%). Significant risk factors for lower body acute injuries were age (OR=2.14; P =.01), previous injury (OR=2.23; P =.01), and an injury at the start of the year (OR=2.56; P =.02). For lower body overuse injuries, gender (OR=2.85; P =.02) and the interval shuttle run test score (OR=2.44; P =.04) were significant risk factors. Previous injury (OR=2.59; P =.04) and injury at the start of the year (upper body: OR=4.57; P =.02; lower body: OR=3.75; P <.01) were risk factors for severe injuries. Injury‐related time loss was positively related to total academic success ( r =.20; P =.02) and success in theoretical courses ( r =.24; P =<.01). No association was found between time loss and academic success for sport courses.